PERNIKAHAN INTERNAL KELOMPOK ISLAM JAMAAH DI YOGYAKARTA: (Perspektif Undang-Undang No 1 Tahun 1974 Dan Kompilasi Hukum Islam) - Hamdan Arief Hanief; Hasman Dzofiri (Sahaja: Journal Sharia and Humanities, 2022)
The large number of religious groups in Indonesia makes all kinds of differences in implementing Islamic law. One of them is the Jamaah Islamic group which in the implementation of their marriage takes two contracts, namely having to take internal marriage (ND) and outside marriage (NL). The focus of this research is: first, what is the procedure for the implementation of internal marriage carried out by Islam Jamaah ?; second, how is the internal marriage of the Jamaah Islamic group in the perspective of Law No. 1 of 1974 and the Compilation of Islamic Law?. This research is a field research (Library Research) which uses qualitative methods with a juridical-normative approach. The conclusions of this study are: first, the implementation of marriage procedures in the Jamaah Islamic environment is quite identical to the marriage patterns of Muslims in general. Like others, Jamaah Islam begins the procedure with matchmaking between congregations by the marriage team, followed by the marriage process until the timing of the marriage contract is executed. The difference is, the Jamaah Islamic Group requires its members to marry fellow Jamaah Muslims. The prospective bride from outside must take a pledge and join the Islamic Jamaah group before being allowed to marry a member of the Islamic Jamaah. Second, there are several differences between the Jamaah Islamic marriage law and the marriage regulated in Law No. 1 1974 and the Compilation of Islamic Laws.